Optimalisasi Manajemen Strategi untuk Pengembangan Pendidikan Nonformal di PKBM Cerdas Mandiri - Jamali; Rizayanti (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
This study aims to describe the strategic management of non-formal education development at the Community Learning Center (PKBM) Cerdas Mandiri. The research employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation, and then analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that the development of non-formal education at PKBM Cerdas Mandiri is carried out through five stages of strategic management: planning, internal and external environmental analysis, strategy formulation, strategy implementation, and evaluation and supervision. The main strategies applied include online learning, community-based programs, free education, and socialization and promotion efforts. The implementation of these strategies demonstrates the institution’s commitment to expanding access, improving quality, and aligning education with community needs. Evaluation and supervision are conducted continuously through academic supervision, monitoring of community-based programs, and oversight of free education initiatives. In conclusion, strategic management at PKBM Cerdas Mandiri is implemented in a directed, participatory, and adaptive manner, enabling the institution to effectively develop non-formal education that is relevant to contemporary demands and community needs.